State of the world's raptors: Distributions, threats, and conservation recommendations. (November 2018) - McClure, Christopher J.W.; Westrip, James R.S.; Johnson, Jeff A.; Schulwitz, Sarah E.; Virani, Munir Z.; Davies, Robert; Symes, Andrew; Wheatley, Hannah; Thorstrom, Russell; Amar, Arjun; Buij, Ralph; Jones, Victoria R.; et al.
Abstract: Raptors provide critical ecosystem services, yet there is currently no systematic, global synthesis of their conservation status or threats. We review the International Union for the Conservation of Nature's Red List to examine the conservation status, distributions, threats, and conservation recommendations for all 557 raptor species. We further assess the significance of Important Bird and Biodiversity Areas (IBAs) for raptor conservation. We also determine which countries contain the most species listed under the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia (Raptors MoU). Raptors, especially Old World vultures, are more threatened than birds in general. Eighteen percent of raptors are threatened with extinction and 52% of raptors have declining global populations. South and Southeast Asia have the highest richness and the largest number of threatened raptor species. By country, Indonesia has the highest richness of raptor species (119) and most declining species (63). China and Russia contain the most Raptors MoU species, although they are not yet signatories to the agreement. Raptor species that require forest are more likely to be threatened and declining than those that do not. Agriculture and logging are the most frequently identified threats, although poisoning is especially detrimental to Old World vultures. Of the 10 most important IBAs for raptors, six are in Nepal. Highest priority conservation actions to protect raptors include preventing mortality and conserving key sites and priority habitats. Improved long-term monitoring would allow for conservation to be appropriately targeted and effectiveness of interventions to be assessed.